A technical overview of supercritical fluid chromatography-mass spectrometry (SFC-MS) and its recent applications in pharmaceutical research and development. (December 2021) - Chen, Liuxi; Dean, Brian; Liang, Xiaorong
Abstract: In this paper, we review the growing development and applications of supercritical fluid chromatography-mass spectrometry (SFC-MS) for the analysis of small molecular analytes and biomarkers in drug discovery. As an alternative chromatographic technique, SFC instrumentation and methodology have dramatically advanced over the last decade. Mass spectrometry (MS) provides the powerful detection capability as it couples with SFC. A growing number of SFC-MS/MS applications were reported over the last decade and the application areas of SFC-MS/MS is rapidly expanding. The first part of this review is devoted to the different aspects of SFC-MS development and recent technological advancements. In the second part of this review, we highlight the recent application areas in pharmaceutical research and development.